Key Concepts in Mental Health / Second Edition - Pilgrim David (Sage Publications, 2009)
An accessible and authoritative knowledge of the essential topics in a variety of disciplines. Acknowledgements, Mental Health and Mental Health Problems, Psychiatric Diagnosis, Psychiatric Epidemiology, Functional and Organic Mental Illnesses, The Myth of Mental Illness, Madness, Sadness, Fear, Personality Disorders, Self-Harm, Substance Misuse, Learning Disability, Causes and Constructs, Physical Health, Well-Being, Pleasure, Creativity, Spirituality, Eating Disorders, Mental Health Services, Primary Care, Careers, Recovery, Coercion, Malpractice, Mental Health and Society, Segregation, Eugenics, Stigma, Work, The Mass Media, Suicide, Social Class, Race, Gender, Age, Childhood Adversity, Warfare.